Revision, uptake and coding issues related to the open access Orchard Sports Injury Classification System (OSICS) versions 8, 9 and 10.1 - John Orchard; Katherine Rae; John Brooks; et al (Dove Medical Press, 2010)
John Orchard1, Katherine Rae1, John Brooks2, Martin Hägglund3, Lluis Til4, David Wales5, Tim Wood61Sports Medicine at Sydney University, Sydney NSW Australia; 2Rugby Football Union, Twickenham, England, UK; 3Department of Medical and Health Sciences, Linköping University, Linköping, Sweden; 4FC Barcelona, Barcelona, Catalonia, Spain; 5Arsenal FC, Highbury, England, UK; 6Tennis Australia, Melbourne, Vic, AustraliaAbstract: The Orchard Sports Injury Classification System (OSICS) is one of the world’s most commonly used systems for coding injury diagnoses in sports injury surveillance systems. Its major strengths are that it has wide usage, has codes specific to sports medicine and that it is free to use. Literature searches and stakeholder consultations were made to assess the uptake of OSICS and to develop new versions. OSICS was commonly used in the sports of football (soccer), Australian football, rugby union, cricket and tennis. It is referenced in international papers in three sports and used in four commercially available computerised injury management systems. Suggested injury categories for the major sports are presented. New versions OSICS 9 (three digit codes) and OSICS 10.1 (four digit codes) are presented. OSICS is a potentially helpful component of a comprehensive sports injury surveillance system, but many other components are required. Choices made in developing these components should ideally be agreed upon by groups of researchers in consensus statements.Keywords: sports injury classification, epidemiology, surveillance, coding